Mediation of Affective Commitment: The Impact of Work Flexibility and Organizational Support on Community Information Performance - Dewi, Asfita; Herlambang, Toni; Martini, Ni Nyoman Putu; Qomariah, Nurul; Ridwan, Wachid (Ilomata International Journal of Social Science, 2025)
With the development of information technology, the need for fast information becomes crucial for government attention. The formation of the Community Information Group (KIM) is a solution to increase public knowledge. This study aims to determine and analyze the influence and support of the organization on the performance of the management of the Community Information Group (KIM) in Jember Regency through affective commitment. This study uses descriptive and verification methods with a quantitative approach. The research sample was 168 respondents selected using purposive sampling techniques from a total population of 672 KIM managers. Data was collected through questionnaires, observations, documentation, and interviews. Data were analyzed using the Structural Equation Model (SEM) with the WarpPLS 8.0 program. The results showed that the minimum work and organizational support significantly affected KIM members' performance and affective commitment. Work flexibility allows members to manage their time and work methods more efficiently, increasing productivity and emotional commitment to the organization. Organizational support improves performance by providing the necessary resources and strengthening members' emotional ties to common goals. Both factors, both directly and through affective commitment, encourage KIM members to work optimally and effectively. The practical implications of this study emphasize the importance of implementing more adaptive work policies to increase alertness and strengthen organizational support through adequate training, resource provision, and rewards. This will create a supportive and empowering work environment, resulting in members who are not only high performers but also have loyalty and dedication to achieving common goals.